(untitled) (Research, Society and Development, 2022)
Beef jerky is a typically Brazilian food product that consists of adding salt (sodium chloride, NaCl) to bovine meat. Salt is used as main preservative when preparing jerked meat, however, certain species of microorganisms, known as halophiles, optimally develop in the presence of high salt concentrations, thus salty food may contain halophiles and cause undesirable alterations in the products. In this context, this study aims to isolate, characterize, and assess the growth parameters of halophilic strains isolated from beef jerky. Two halophilic strains were isolated: C11 strain, with cocci-shaped morphological features from white cream color, and V22 strain, with red pleomorphism. Both the lineages were gran-negative, catalase, and oxidase positive, with optimum growth time after 15 incubation days at 37 °C. The strains were neutrophilic, growing only at pH 7.0 and subjected to a 2x3 factorial experimental design to assess and optimize the growth of strains at different concentrations of NaCl, MgCl2, and yeast extract. We found that for both the optimal growth conditions, the studied variables ranged from 25 to 35 g L-1 of MgCl2, 5 g L-1 of yeast extract, but for NaCl, the C11 strain did not grow in medium containing 300 g L-1 (optimally at 200), while the V22 showed no growth in medium containing 100 g L-1 (optimally at 300). Therefore, the features of the isolates suggest that they belong to the Halobacteriaceae family.